Spatial County Planning as a Regional Legitimating Process - Roar Amdam (European Journal of Spatial Development, 2004)
In Norway’s new regional policy setup the 19 county municipalities have been given a key role as regional planning and development actors. This is not however a completely new role for the counties, though their role has undoubtedly been strengthened, while at the same time the locus of national regional development policy seems to have moved from government to governance. This change of policy implies that the regional planning and development work done by the counties must be a collaborative process between the international, national, regional and local levels, and between the public, private and voluntary sectors. In a regional policy process based on governance however, the counties will not be the only regional development actors. They have to cooperate and compete with other established and newly created regional development actors and agencies in order to become political legitimate institutions. As far as we have scientific knowledge about how the counties will fulfil their role, we believer that they can only do the best they can within the room for manoeuvre bequeathed to them in the context of the actual political power structure adopted. In this paper we will discuss county planning in the context of the formation of ‘political will’ seeing it as a legitimating process, focusing in the main on the interaction between the state level and the local authorities. As far as can be seen from a ‘political legitimacy’ perspective, this process is incomplete, lacking in particular the juridical discourses of national state support for the counties through the delivery of legal acceptance and the economic tools designed for the role of regional development actor. Thus the process fails to fulfil the legitimating ‘bottom up’ process, while in addition failing to bestow county planning with the necessarily level of ‘top down’ legitimacy and acceptance. As long as this weakness exists in county planning, the counties will suffer from a ‘power deficit’ as they will continue to lack the very tools needed to become powerful regional development actors in the new regional policy framework.